Relationship Between Accessibility to Health Services with Exclusive Breastfeeding - Fauziah, Nuraini (Journal of Global Research in Public Health, 2023)
Globally, the prevalence of exclusive breastfeeding is still less than 40%. Exclusive breastfeeding is the appropriate recommendation to build quality human resources. The infant mortality rate has not decreased according to the SDGs target. Neonatal death rate is 32/1000 live births. Difficulties in accessing health services can also be seen in Maternal and Child Health (MCH) program, where the MMR and IMR in several areas are still quite high. This study aims to determine the relationship between accessibility to health services related to exclusive breastfeeding. This study is a quantitative study with a cross-sectional analytic design. Primary data collection in the province of DKI Jakarta. Data collected and analyzed using SPSS 25 as univariate and bivariate analysis. The results showed that there was a relationship between the accessibility to health services with exclusive breastfeeding (p=0.040). Accessibility to health services is positively related to exclusive breastfeeding for infants. Ease of access to health services is the fulfillment of all items of access to health services that should be easily accessible to mothers. The item availability of health workers around the house (p=0.042) and health workers who examine mothers during childbirth (p=0.0001) had the greatest influence on access to health services so that it had a positive effect on exclusive breastfeeding. Ease of access to health services motivates and helps a mother to provide exclusive breastfeeding to her baby. We hope that access to health services and facilities can improve performance in providing easy access and the best services for mothers.